Harmonizing light transmission aggregometry in the Netherlands by implementation of the SSC-ISTH guideline. (19th May 2021) - Munnix, I.C.A.; Van Oerle, R.; Verhezen, P.; Kuijper, P.; Hackeng, C.M.; Hopman-Kerkhoff, H.I.J.; Hudig, F.; Van De Kerkhof, D.; Leyte, A.; De Maat, M.P.M.; Oude Elferink, R.F.M.; Ruinemans-Koerts, J.; et al.
Abstract: Light transmission aggregometry (LTA) is considered the gold standard method for evaluation of platelet function. However, there are a lot of variation in protocols (pre-analytical procedures and agonist concentrations) and results. The aim of our study was to establish a national LTA protocol, to investigate the effect of standardization and to define national reference values for LTA. The SSC guideline was used as base for a national procedure. Almost all recommendations of the SSC were followed e.g. no adjustment of PRP, citrate concentration of 109 mM, 21 needle gauge, fasting, resting time for whole blood and PRP, centrifugation time, speed and agonists concentrations. LTA of healthy volunteers was measured in a total of 16 hospitals with 5 hospitals before and after standardization. Results of more than 120 healthy volunteers (maximum aggregation %) were collected, with participating laboratories using 4 different analyzers with different reagents. Use of low agonist concentrations showed high variation before and after standardization, with the exception of collagen. For most high agonist concentrations (ADP, collagen, ristocetin, epinephrine and arachidonic acid) variability in healthy subjects decreased after standardization. We can conclude that a standardized Dutch protocol for LTA, based on the SSC guideline, does not result in smaller variability in healthy volunteers for all agonist concentrations.